Effects of Feeding Adults of Hermetia illucens (Diptera: Stratiomyidae) on Longevity, Oviposition, and Egg Hatchability: Insights Into Optimizing Egg Production. Issue 1 (11th February 2019) - Bertinetti, Cesar; Samayoa, Ana Clariza; Hwang, Shaw-Yhi
Abstract: Larvae of the black soldier fly, Hermetia illucens (L.), have been widely studied for their capacity of generating value-added products through waste bioconversion. Several efforts have been made towards optimization of rearing methods of the larval stages. Despite this, less information regarding the feeding behavior of adults and its effects on life parameters is available. We studied the impacts of subjecting adults to four diets: no diet (control); drinking water (water); a mix of sugar, bacteriological peptone, and milk powder (milk); and agar with sugar (agar). In total five replicates with 50 females and 50 males per treatment were performed. Oviposition and mortality were recorded daily. Additionally, egg hatchability and number of eggs per mass were measured. Results from this study indicate that the amount of eggs was 3 times higher for diets containing a protein source. Furthermore, milk treatment increased the oviposition period by 10 d compared with that of the standard water treatment. No significant difference was found for male longevity; however, females fed with milk diet lived 5 d longer than the control group. Egg hatchability ranged 70–85%, but was not significantly different across treatments. In terms of egg production for both industrial and research purposes, we suggest using a protein-rich diet to maximize oviposition and longevity parameters as adults do benefit from feeding.